Brain cortical maturation assessed by magnetic resonance imaging in unaffected or mildly affected fetuses with cytomegalovirus infection. (17th April 2023) - Hawkins‐Villarreal, A.; Moreno‐Espinosa, A. L.; Castillo, K.; Hahner, N.; Picone, O.; Mandelbrot, L.; Simon, I.; Gratacós, E.; Goncé, A.; Eixarch, E.
ABSTRACT: Objectives: To assess by magnetic resonance imaging (MRI) the cortical maturation pattern in fetuses with cytomegalovirus (CMV) infection with mild or no abnormalities on ultrasound (US) and MRI, and to establish possible differences compared with healthy controls. Methods: This was a retrospective case–control study of consecutive pregnancies with a CMV‐infected fetus undergoing prenatal MRI as a complementary diagnostic tool in two centers, and a control group of singleton low‐risk pregnancies without fetal structural abnormalities, with normal fetal growth and with healthy newborns. CMV infection was confirmed by extraction of CMV‐DNA from fetal and neonatal samples. Only fetuses with mild (mildly affected) or no (unaffected) neuroimaging abnormalities on US and MRI were included. MRI measurements of fetal parieto‐occipital sulcus, cingulate sulcus and calcarine sulcus depth, Sylvian fissure depth and Sylvian fissure angles were performed and cortical development grading of specific cortical areas and sulci were assessed by one operator who was blinded to CMV infection status. Data were compared between controls and fetuses with CMV infection, using linear regression and non‐parametric trend analysis. Results: Twenty‐four CMV‐infected fetuses (seven unaffected and 17 mildly affected) and 24 healthy controls that underwent fetal MRI between 27 and 36 weeks' gestation were included. Compared with controls, CMV‐infected fetuses showed significantly larger median lateral ventricular width (right side, 7.8 (interquartile range (IQR), 5.9–9.9) mm vs 3.9 (IQR, 2.6–5.3) mm; left side, 7.5 (IQR, 6.0–10.9) mm vs 4.2 (IQR, 3.2–5.3) mm), significantly decreased parieto‐occipital sulcus depth (right side, 12.6 (IQR, 11.3–13.5) mm vs 15.9 (IQR, 13.5–17.3) mm; left side, 12.3 (IQR, 10.6–13.5) mm vs 16.0 (IQR, 13.3–17.5) mm) and calcarine sulcus depth (right side, 15.4 (IQR, 14.4–16.3) mm vs 17.5 (IQR, 16.1–18.7) mm; left side, 14.6 (IQR, 14.1–15.6) mm vs 16.7 (IQR, 15.6–18.9) mm) ( P  < 0.001 for all). Compared with controls, CMV‐infected fetuses also had significantly smaller upper (right side, 42.8° (IQR, 35.8–45.8°) vs 48.9° (IQR, 38.4–64.7°); left side, 40.9° (IQR, 34.2–45.8°) vs 48.2° (IQR, 41.9–60.7°)) and lower (right side, 41.6° (IQR, 34.4–49.2°) vs 48.9° (IQR, 40.6–60.9°); left side, 42.2° (IQR, 38.8–46.9°) vs 48.9° (IQR, 39.5–57.5°)) Sylvian fissure angles ( P  < 0.05 for all). In addition, the mildly affected CMV‐infected fetuses had a significantly lower cortical development grading in the temporal and parietal areas, and the parieto‐occipital and calcarine sulci compared with healthy fetuses ( P  < 0.05). These differences persisted when adjusting for gestational age, ipsilateral atrium width, fetal gender and when considering small‐for‐gestational age as a confounding factor. Conclusions: Unaffected and mildly affected CMV‐infected fetuses showed delayed cortical maturation compared with healthy controls. These results suggest that congenital CMV infection, even in non‐severely affected fetuses that are typically considered of good prognosis, could be associated with altered brain cortical structure. Further research is warranted to better elucidate the correlation of these findings with neurodevelopmental outcomes. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.